Forest cover outweighs restoration strategy in explaining Euglossini beta diversity in the Atlantic Forest, Brazil - da Silva Carneiro, Lázaro; Ribeiro, Milton Cezar [UNESP]; Ricketts, Taylor; Martello, Felipe; Frantine-Silva, Wilson; Gaglianone, Maria Cristina (Elsevier, 2025)
Ecosystem restoration is essential to recover biodiversity and to maintain ecosystem services. The outcomes of active and passive restoration strategies should be evaluated through ecological indicators, of which bees have been widely used. Orchid bees (Euglossini) are essential pollinators in Neotropical ecosystems and respond negatively to landscape disturbances. Understanding how forest cover (%) and landscape heterogeneity influence their communities is essential for guiding restoration efforts. Moreover, assessing how active restoration and natural regeneration shape the orchid bee community recovery compared to forest control sites is crucial for conservation strategies. We analyzed the effects of restoration strategy (active restoration and natural regeneration), forest cover (%), and landscape compositional heterogeneity on species composition and beta diversity components of euglossine communities in the Atlantic Forest, Brazil. We found that forest cover (%) and landscape heterogeneity significantly influence species composition, turnover, and nestedness, while restoration strategy has no significant effect on bee communities. Landscapes with a higher forest cover (> 50 %) supported forest-dependent species, while a low forest cover (< 25 %) favored species with higher environmental plasticity. The turnover and nestedness components responded differently to variations in forest cover (%) and landscape heterogeneity, depending on the sites pairwise. In addition, while assessing the effect of forest cover (%) on species occurrence probability, we found a positive response for some euglossine bees, such as Euglossa iopoecila and Euglossa ignita. These results emphasize the role of forest restoration, regardless of the strategy, in recovering euglossine regional diversity and reestablishing ecosystem services. Our findings highlight the importance of increasing forest cover at the landscape scale to enhance the outcomes of active restoration and natural regeneration strategies, thereby supporting restoration success and biodiversity conservation in fragmented tropical landscapes.